Effect of Aspergillus and Bacillus Concentration on Cotton Growth Promotion - Escobar Diaz, Paola Andrea; dos Santos, Roberta Mendes; Baron, Noemi Carla; Gil, Oniel Jeremias Aguirre; Rigobelo, Everlon Cid (Frontiers in Microbiology, 2021)
There are no studies in literature on the effect of inoculant concentrations on plant growth promotion. Therefore, in the present study, two experiments were carried out, one under pot conditions and the other in the field with cotton crop in order to verify the effect of Aspergillus and Bacillus concentrations on the biometric and nutritional parameters of plant and soil, in addition to yield. The pot experiment evaluated the effect of different concentrations, ranging from 1x104 to 1x1010 colony-forming units per milliliter (CFU mL-1) of microorganisms B. velezensis (Bv188), Bacillus subtilis (Bs248), B. subtilis (Bs290), Aspergillus brasilense (F111), Aspergillus sydowii (F112) and Aspergillus sp versicolor section (F113) on parameters plant growth promotion and physicochemical and microbiological of soil. Results indicated that the different parameters analyzed are influenced by the isolate and microbial concentrations in a different way, and allowed the selection of four microorganisms (Bs248, Bv188, F112 and F113) and two concentrations (1x104 and 1x1010 CFU mL-1), which were evaluated in the field to determine their effect on yield. The results show that, regardless of isolate, inoculant concentrations promoted the same fiber and seed cotton yield. These results suggest that lower inoculant concentrations may be able to increase cotton yield, eliminating the need to use concentrated inoculants with high production cost.